Pengaruh Temperatur dan Waktu Sludging Heavy Fuel Oil terhadap Efisiensi Kerja Fuel Oil Purifier di MV. Pos Logistics 2 - Bakar, Abu; Adnan; Saleh, Muhammad; Alet, I Made; Andriani, Suci (Politeknik Pelayaran Barombong, 2025)
This research aims to determine the influence of fuel temperature and fuel sludging time entering the purifier for the purification process and to find out what the fuel temperature settings are and the slugging time to get the maximum purifier clock. The methods used in the research are research experimental, which is descriptive quantitative in nature. The samples taken were HFO purifier working hours data on board MV. Pos Logistic 2 by using tables and graphs quantitative analysis of quantities total hours worked when operated . This research set the temperature and sludging time when operating. The results of the study show the maximum working hours of the HFO purifier on board the MV. Pos Logistic 2 are determined by the temperature setting of the heavy fuel oil entering the purifier and the sludging time setting. Setting temperature and time of HFO purifier sludging from the research results found achievement the maximum working hours for an HFO purifier are when setting a temperature of 90oC and fifty minute sludging time setting (50’). It is known that the results the achievement of working hours for 15 days of data collection reached 362 hours, the maximum working hours presentation amount was 91% of the total working hours standardized in the manual book of 400 hours. The results of this study are suggested to get the maximum working hours when operating a Heavy Fuel Oil Purifier using 380 Cst Heavy Fuel Oil fuel, the temperature setting to enter the furifier is 90oC, the sludging time is 50 minutes and the ship's officers (engine officers) must be able and pay attention to adjustments and settings in the digital control device of the purification system, when changing the use of the type of fuel used on board the ship so that the achievement of Heavy Fuel Oil Purifier working hours can be maximized according to the manual.